WEWENANG DIREKSI PERUSAHAAN PERSEROAN DAERAH (PERSERODA) TIDAK TERLEPAS DARI PERAN SERTA ORGAN PERSEROAN - Endang Suratminingsih (Problematika Hukum, 2019)
BUMD organs (Regional Owned Enterprises) in regional company companies consist of a general meeting of shareholders (GMS); commissioner; and directors. The GMS is a company organ with powers not granted to the Board of Directors or the Board of Commissioners within the limits specified in the Job Creation law and/or the articles of association. The commissioner is tasked with supervising the regional state-owned companies and supervising and providing advice to the directors in running the management of the company, although in certain cases the directors are not authorized to represent the company. However, the condition of Perseroda's governance is still not optimal, as can be seen from the presence of bureaucratic work patterns that lead to actions by the directors beyond their authority, this causes the authority of the directors to take actions for the interests of the company not optimally and the function of the commissioners as supervisors does not work according to their authority. To answer the problem the theory used is the GONE theory which was introduced by Jack Bologne Gone where the position of directors is very prone to carry out acts of self-enrichment due to the inherent authority for directors in representing the company that is unlimited and unconditional. It can be concluded that there is a compromise between the role of directors and the role of commissioners in corporate governance. Good Corporate Governance (GCG) is only considered as a company logo (symbol). Therefore, it is suggested that shareholders are expected to form a special team of professional experts in their field consisting of BUMD coaches/practitioners/academicians/entrepreneurs to select candidates for company management in order to produce a director and commissioner who has concern and good faith ability, honest loyalty to the company with a degree of high knowledge in the field of business,